[BP.07.04] THE SNAP-HT TRIAL: SELF-MANAGEMENT OF ANTIHYPERTENSIVE MEDICATION POSTPARTUM – CAN WOMEN DO IT BETTER?. (September 2017) - McManus, R.; Cairns, A.; Tucker, K.; Leeson, P.; Mackillop, L.; Crawford, C.; Baker, N.; Tebbutt, J.
Abstract : Objective: Hypertensive disorders of pregnancy (HDP) affect one in ten pregnancies. Hypertension may persist postpartum, when complications can occur but blood pressure tends to reduce back to pre-pregnancy levels over 3–6 months. In essential hypertension, the TASMINH2 and TASMIN-SR studies showed that self-management significantly improved blood pressure (BP) compared to usual care. The SNAP-HT study applied a similar rationale to test self-titration of antihypertensives following a hypertensive pregnancy in a feasibility trial. Figure. No caption available. Design and method: Postnatal women, taking antihypertensive medication, were randomly allocated to self-management or standard care and followed up for six months. Self-management entailed daily home BP monitoring. Readings were submitted to a mobile phone-based telemonitoring system that provided automatic feedback and included an individualised medication reduction schedule. The primary outcome was feasibility, with secondary outcomes including BP control and safety. Results: 91/188 (48%) women approached were both eligible and consented to randomisation (45:46 intervention:control). Their mean age was 32y (SD 5), mean body mass index 29 kg/m 2 (SD 8), and mean baseline BP (day 1–6 postpartum) 133/86mmHg (SD 14/10 respectively). 75/91 (82%) were white British. Index of Multiple Deprivation scores were available for 88/91: 52/88 (59%) 1st/2nd quintiles, 23/88 (26%) 3rd quintile and 13/88 (15%) 4th/5th quintiles. Follow-up is complete with 82/91 (90%) retention, and 9/91 (10%) withdrawals. Considering complete cases: compliance with the trial was 403/410 (98%) scheduled follow-up visits; 36/40 (90%) participants (intervention group) submitted BP readings on at least alternate days whilst on treatment (NICE recommendation); 1075/1513 (71%) expected daily readings (on treatment) were submitted. Secondary outcome data including blood pressure will be available in early 2017 in time for presentation at the conference. Conclusions: The SNAP-HT trial will provide the first randomised controlled evaluation of BP self-management postpartum. The recruitment (approximately 50% of those approached) and retention rates (90%) suggest expanding this study to a larger scale would be practicable. An early indication of the likely efficacy will be available once analysis is complete and will be presented at the conference.